2015
DOI: 10.1016/j.jfluchem.2015.06.005
|View full text |Cite|
|
Sign up to set email alerts
|

Synthesis of 3,3,3-trifluoroethyl isocyanate, carbamate and ureas. Anticancer activity evaluation of N-(3,3,3-trifluoroethyl)-N′-substituted ureas

Abstract: A new method is described for producing 3,3,3-trifluoroethyl isocyanate from perfluoroisobutene (PFIB). Isocyanate was used for synthesis of carbamates and ureas. A series of trifluoroethyl-substituted ureas has been tested in the National Cancer Institute (NCI, Bethesda, USA) by the NCI-60 DTP Human Tumor Cell Line Screening Program at a single high dose (10−5 M). The moderate anticancer activity was shown against some types of cancer on the individual human cell lines for leukemia, non-small cell lung cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…These disciplines vary from pharmacology [46] to molecular imaging [7, 8], the latter of which includes a promising new technique known as Cerenkov imaging [912]. Our fluorine-related research is focused on the synthesis of novel potential anticancer drugs [1318] and the development of 18 F-labeled Cerenkov imaging agents [1923]. Recently, we reported that direct electrophilic fluorination with dilute fluorine gas under acidic conditions is a useful method for labeling of triarylmethane-based pH indicators with the positron emitting isotope 18 F [1921] for in vivo pH measurement [22] by a combination of optical Cerenkov imaging and nuclear positron emission tomography (PET).…”
Section: Introductionmentioning
confidence: 99%
“…These disciplines vary from pharmacology [46] to molecular imaging [7, 8], the latter of which includes a promising new technique known as Cerenkov imaging [912]. Our fluorine-related research is focused on the synthesis of novel potential anticancer drugs [1318] and the development of 18 F-labeled Cerenkov imaging agents [1923]. Recently, we reported that direct electrophilic fluorination with dilute fluorine gas under acidic conditions is a useful method for labeling of triarylmethane-based pH indicators with the positron emitting isotope 18 F [1921] for in vivo pH measurement [22] by a combination of optical Cerenkov imaging and nuclear positron emission tomography (PET).…”
Section: Introductionmentioning
confidence: 99%
“…According to a COMPARE analysis [38] of microarray-based transcriptome-wide mRNA expressions, 21 genes were found to be significantly correlated with the response of 60 tumor cell lines to cantharidin. Some researchers screened their synthetic compounds against human cancer cell lines and used a COMPARE analysis to evaluate the anticancer activity and predict the probable mechanism [27,39,40,41,42]. Therefore, the following studies examined the possible mechanism using a standard NCI-60 test and COMPARE analysis of 5a .…”
Section: Resultsmentioning
confidence: 99%
“…Recently, urea derivatives obtained from sulfamethoxazole (SMX) 1 have been proposed as potential inhibitors of human carbonic anhydrases [ 11 ], anticancer [ 12 , 13 ], and antimicrobial agents [ 14 , 15 ]. Importantly, we reported the synthesis and antimicrobial activity of nine sulfamethoxazole-based ureas and corresponding cyclic analogues, imidazolidine-2,4,5-triones.…”
Section: Introductionmentioning
confidence: 99%